Multicultural values in ELT textbook for Indonesian elementary schools: a critical discourse analysis - Dalimunte, Ahmad Amin; Suryani, Irma (JOALL (Journal of Applied Linguistics and Literature), 2025)
Incorporating cultural elements into teaching is essential for Indonesian educators. However, a key issue currently observed is the lack of awareness among English teachers regarding the integration of cultural learning into English instruction. This study was to critically investigate how culture is represented and introduced in an English textbook at the elementary level. Cultural contents were analyzed throughout the 2021 revised edition of the English textbook for grade 5 of elementary school, published by the Ministry of Education and Culture (MOEC). The textbook was selected due to its widespread use in Indonesian schools and its production by MOEC. To analyze the data, a semiotic critical discourse analysis approach was employed on the basis of Kachru's concentric circle framework. Moran's 4P framework, addressing products, practices, perspectives, and people, as well as Bennett's theory on cultural values, were also used to further investigate the cultural dimensions presented in the textbook. The findings revealed a significant dominance of source culture content, while the representation of target culture and foreign culture was minimal. Of the 27 cultural views analyzed, expanding circle cultures were most prevalent. Our findings also indicated that product culture was the most prominent cultural dimension. The findings suggested that cultural embedment in the textbook facilitates students to have a broader perspective of diverse culture. Recognizing and understanding the multicultural values and their representations allows Indonesian students to develop their intercultural competence, which not only introduces them to diverse cultures but also strengthens their communication skills.